Cleft Rhinoplasty: Strategies for the Multiply Operated Nose - Hsieh, Tsung-yen; Dedhia, Raj; Tollefson, Travis T. (Facial Plastic Surgery, 2018)
Rhinoplasty, as a surgical procedure to improve the appearance of the nose while preserving or improving function, is complicated and difficult to master. Revision cleft rhinoplasty offers another tier of challenge. The symmetry, proportions, and definition of the nose are affected by the native cleft deformity but also previous surgical scars, cartilage grafts, and skin excisions. Our preferred approach is to use structural cartilage grafting to establish septal and lower lateral cartilage resiliency. Internal lining deficiency is addressed with skin or lining transfer, while excess nasal tip thickness is contoured to improve definition. Of the utmost importance, the cleft nasal deformity cannot be considered in isolation, but rather a combined amalgamation of the lip muscle and scar, dentofacial occlusion, and skeletal maxillary deficiency.
Keywords: rhinoplasty; cleft lip; cleft nasal deformity; revision; cartilage graft